Cognitive behavioral group therapy versus psychoeducational intervention in Parkinson’s disease - Berardelli I (Dove Medical Press, 2018)
Isabella Berardelli,1 Maria Carmela Bloise,2 Matteo Bologna,2,3 Antonella Conte,2,3 Maurizio Pompili,1 Dorian A Lamis,4 Massimo Pasquini,2 Giovanni Fabbrini2,3 1Department of Neurosciences, Mental Health and Sensory Organs, Suicide Prevention Center, Sant’Andrea Hospital, Sapienza University of Rome, Rome, 2Department Human Neurosciences, Sapienza University of Rome, Rome, 3Neuromed Institute (IRCCS), Pozzilli (IS), Italy; 4Department of Psychiatry & Behavioral Sciences, Emory University School of Medicine, Atlanta, GA, USA Objective: The aim of the current study was to evaluate whether cognitive behavioral group therapy has a positive impact on psychiatric, and motor and non-motor symptoms in Parkinson’s disease (PD).Methods: We assigned 20 PD patients with a diagnosis of psychiatric disorder to either a 12-week cognitive behavioral therapy (CBT) group or a psychoeducational protocol. For the neurological examination, we administered the Unified Parkinson’s Disease Rating Scale and the non-motor symptoms scale. The severity of psychiatric symptoms was assessed by means of the Hamilton Depression Rating Scale, the Hamilton Anxiety Rating Scale, the Brief Psychiatric Rating Scale, and the Clinical Global Impressions.Results: Cognitive behavioral group therapy was effective in treating depression and anxiety symptoms as well as reducing the severity of non-motor symptoms in PD patients; whereas, no changes were observed in PD patients treated with the psychoeducational protocol.Conclusion: CBT offered in a group format should be considered in addition to standard drug therapy in PD patients. Keywords: Parkinson’s disease, cognitive behavioral group therapy, psychoeducation, motor symptoms, non-motor symptoms